Can parental migration reduce petty corruption in education? - Lisa Sofie Höckel; Manuel Santos Silva; Tobias Stöhr (Kiel Institute for the World Economy (IfW), 2015)
Educational outcomes of children are highly dependent on household and school-level inputs. In poor countries, remittances from migrants can provide additional funds for the education of the left behind. At the same time the absence of migrant parents can affect families' time allocation towards education. Previous work on education inputs often implicitly assumed that preferences for different kinds of education inputs remain unchanged when household members migrate. Using survey data from Moldova, one of the countries with the highest emigration rates in the world, and an instrumental variable approach we find that the strongest migration-related response in private education expenditure are substantially lower informal payments to public school teachers. This fact is at odds with a positive income effect due to migration. We argue that our results are likely to be driven by changing preferences towards educational inputs induced by migration.
Keywords: F22; I22; D13; H52; 330; migration; emigration; education spending; social remittances; corruption; children left behind